2013
DOI: 10.1159/000346273
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion Effect on in vivo Percutaneous Penetration of Chemicals in Man and Monkey: Partition Coefficient Effects

Abstract: Background/Aim: Skin occlusion can increase the hydration of the stratum corneum up to 50%, which can have substantial effects on the percutaneous absorption of penetrants by altering skin barrier physiology. Though occlusion is widely utilized to enhance the penetration of applied drugs in clinical practice, it is not well known for which chemicals occlusion enhances the penetration through skin. In this review, we focus on what effect occlusion has on the percutaneous absorption of compounds of varying lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…It also seems likely that occlusion by the sebum film (height approx. 20 µm) could have hydrated the skin and potentiated the transdermal flux [52, 53]. We note that there may also be a chemical-specific skin penetration enhancement effect from the oleic acid present at a high level (30%) in the artificial sebum.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It also seems likely that occlusion by the sebum film (height approx. 20 µm) could have hydrated the skin and potentiated the transdermal flux [52, 53]. We note that there may also be a chemical-specific skin penetration enhancement effect from the oleic acid present at a high level (30%) in the artificial sebum.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The largest differences in C p, ss values were obtained from switching between occlusion and non-occlusion and water-diluted (with 90% water) vs. neat application. Occlusion increases skin penetration of many compounds due to increased hydration of the stratum corneum and, in the case of volatile compounds, prevention of evaporation (Hafeez and Maibach 2013 ). The presence of a large volume of water in the 90% dilution affected the C p, ss of the most hydrophilic and water-soluble chemicals (DGMME, DMF and 2-ME) to the greatest extent.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, LP is a non-polar solvent, creating an occlusive barrier onto the membrane. It was demonstrated that the occlusion effect is widely used to enhance the penetration of applied drugs in clinical practice [33]. However, occlusion does not increase percutaneous absorption of all chemicals, being more effective for lipid-soluble, non-polar molecules but less efficient for polar molecules, which is the case of MH [34].…”
Section: Resultsmentioning
confidence: 99%